2007
DOI: 10.1074/jbc.m706242200
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Receptor-dependent Activation of Inducible Nitric-oxide Synthase by ERK-mediated Phosphorylation of Ser745

Abstract: Nitric oxide (NO) is a pleiotropic regulator of vascular function, and its overproduction by inducible nitric-oxide synthase (iNOS) in inflammatory conditions plays an important role in the pathogenesis of vascular diseases. iNOS activity is thought to be regulated primarily at the level of expression to generate "high output" NO compared with constitutive NO synthases. Here we show iNOS activity is acutely up-regulated by activation of the B 1 -kinin receptor ( to Asp resulted in a basally hyperactive iNOS wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
63
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 49 publications
7
63
0
1
Order By: Relevance
“…However, B1R signaling also has numerous beneficial effects, such as promoting angiogenesis and neovascularization during wound healing (62)(63)(64), protecting kidneys from renal fibrosis and attenuating cardiac remodeling in stroke-prone spontaneously hypertensive rats (65,66), and reducing lethality in a porcine model of endotoxic shock (67). B1R stimulation also results in high output NO production in human endothelial cells (21,22) via activation of extracellular signal-regulated kinase and acute stimulation of inducible nitric-oxide synthase activity via phosphorylation of Ser 745 (23). One outcome of high output NO production in endothelial cells is inhibition of protein kinase C⑀ activity (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, B1R signaling also has numerous beneficial effects, such as promoting angiogenesis and neovascularization during wound healing (62)(63)(64), protecting kidneys from renal fibrosis and attenuating cardiac remodeling in stroke-prone spontaneously hypertensive rats (65,66), and reducing lethality in a porcine model of endotoxic shock (67). B1R stimulation also results in high output NO production in human endothelial cells (21,22) via activation of extracellular signal-regulated kinase and acute stimulation of inducible nitric-oxide synthase activity via phosphorylation of Ser 745 (23). One outcome of high output NO production in endothelial cells is inhibition of protein kinase C⑀ activity (24).…”
Section: Discussionmentioning
confidence: 99%
“…This is of potential importance in inflammatory or pathological responses. For example, B1R activation stimulates extracellular signal-regulated kinase phosphorylation, prostaglandin production (20), and inducible nitric-oxide synthase-mediated high output NO production (21)(22)(23), which inhibits protein kinase C⑀ activity in endothelial cells (24).…”
mentioning
confidence: 99%
“…Moreover, it is generally held that vascular inflammation leads to reduced bioavailability of eNOS-derived NO and eNOS "uncoupling," accompanied by induction of endothelial iNOS expression, which is the source of high, uncontrolled NO that further exacerbates the disease process (10). However, we have found that iNOS activity in inflamed human endothelium can be increased 3-5-fold beyond its basal level by G protein-coupled receptor signaling (11)(12)(13), and accumulating evidence indicates that eNOS could also play an "iNOS"-type role in inflammation, but the mechanisms have not been defined (14).…”
Section: Nos1) Inducible Nos (Inos Nos2) and Endothelial Nos (Enosmentioning
confidence: 51%
“…In healthy endothelium, the kinin B2R activates eNOS resulting in a short burst of Ca 2ϩ -dependent NO production (20,21). Under inflammatory conditions, endothelial B1R stimulation leads to acute activation of iNOS via ERK1/2-dependent phosphorylation at Ser 745 and prolonged and high output NO production (11)(12)(13). However, signaling pathways for endothelial B2R-dependent NO production under inflammatory conditions have not been investigated.…”
Section: Nos1) Inducible Nos (Inos Nos2) and Endothelial Nos (Enosmentioning
confidence: 99%
“…Jones et al have indicated the importance of calcium/ calmodulin-dependent protein kinase II in regulating iNOS trafficking and activity in VSM cells [77]. Activation of the inducible kinin B 1 receptor stimulates the production of NO in cytokine-treated human lung microvascular endothelial cells [131] and Zhang and coworkers have recently identified ser745 as a physiologically relevant -ERK-dependentphosphorylation site on human iNOS that enhances NO production [174]. These studies would indicate acute regulation of iNOS activity in human cells that express low levels of iNOS.…”
Section: Regulation Of Inos Activity and Expressionmentioning
confidence: 99%